GMP-grade nanoparticle targeted to nucleolin downregulates tumor molecular signature, blocking growth and invasion, at low systemic exposure - Fonseca, Nuno A. (2021)
Patients with breast or ovarian cancer have not benefited from improved efficacy with pegylated liposomal doxorubicin relative to free drug, likely due to the limited extent of the enhanced permeability and retention (EPR) effect, further compromising drug bioavailability in the tumor. Herein it is hypothesized that targeting nucleolin overexpressed in tumor endothelial cells (readily accessible from the vascular compartment), besides cancer cells, with PEGASEMP (doxorubicin hydrochloride in a lipid-based pegylated nanoparticle functionalized with a 31-aminoacid peptide targeting nucleolin), lessens the dependence on high systemic exposures and EPR effect for successful tumor targeting. This strategy has resulted in improved intracellular tumor bioavailability of doxorubicin, at low systemic exposure, associated with a safe toxicological profile. Levels of cell surface nucleolin dictated the antitumor activity of PEGASEMP against nucleolin-overexpressing solid tumors of diverse histological origin, evidencing a significant growth inhibition of malignant mesothelioma over the standard of care. Those observations were paralleled by an impairment of the nucleolin-positive vasculature and downregulation of typically overexpressed genes. Patient stratification based on nucleolin mRNA expression correlated with prognosis and enabled identification of breast and mesothelioma tumors that may potentially benefit from PEGASEMP. Overall, a novel principle of drug delivery is presented with potential therapeutic impact across nucleolin-overexpressing human cancers.